Economic analysis of tilapia farming in some selected area of Dinajpur District: A comparison between monoculture and polyculture: Economic analysis of tilapia monoculture and polyculture - Ferdoushi, Zannatul; Patwary, Zubaida Parveen; Ara, Yeasmin; Rana, Masud (Journal of the Bangladesh Agricultural University, 2019)
The study was conducted to assess the cost and return from tilapia farming. Fifty homestead aquaculture ponds practicing monoculture and polyculture of tilapia (25 farmers from each category) were selected for this study. Data had been collected through face to face interview by using a structured questionnaire during April to September 2015 from the selected farmers of Dinajpur districts. The results from the survey revealed that both the tilapia monoculture and polyculture farming were profitable. However, the average total cost per hectare per production period was found higher (Tk. 332,712.08) in tilapia monoculture than tilapia culture with carps (Tk. 241,722.34). Moreover, the net margin was also found higher in tilapia monoculture with benefit cost ratio 1.51. Whereas, the benefit cost ratio in polyculture farming was 1.34. J. Bangladesh Agril. Univ. 17(1): 117–121, March 2019